Antiviral distribution data – a potential syndromic surveillance system to assist pandemic health service operational planning - Way, Andrew SC; Durrheim, David N; Merritt, Tony; Vally, Hassan (Communicable Diseases Intelligence, 2010)
A pilot study was conducted in rural northern New South Wales from 15 July to 28 August 2009, during Australia's Protect Phase response to the Influenza A H1N1 California 7/09 pandemic. This study explored the feasibility of using administrative data, generated from the distribution of stockpiled antivirals, as a syndromic surveillance system. The purpose was to identify recently affected towns or those with increasing influenza-like illness activity to assist in rural health service operational planning. Analysis of antiviral distribution data was restricted to 113 general practices in rural parts of the Hunter New England Area Health Service. By 2 September 2009 a total of 6,670 courses of antivirals for adults, of which 455 courses were replacement orders, had been distributed to these general practices. Distribution of replacement antivirals were mapped to local government areas on a weekly basis. The syndromic surveillance system delivered timely data on antiviral distribution; used readily available software to generate visual activity maps in less than 30 minutes; proved adaptable; was of low cost; and was well received by health service planners. Full evaluation of the system's utility was limited by the relatively large initial distribution of antivirals and the brief nature of Australia's first pandemic wave. The pilot study demonstrated that a syndromic surveillance system based on distribution of supplies, such as treatment or vaccines, can support local health service operational planning during health emergencies. Commun Dis Intell 2010;34(3):303–309.